Hunger prize award - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Africa Prize for Leadership annually honours a distinguished African who has exhibited exceptional leadership in bringing about the sustainable end of the persistence of hunger at the national, regional or continent-wide level. This year for...